Transitional care interventions reduce unplanned hospital readmissions in high-risk older adults - Kathleen Finlayson; Anne M. Chang; Mary D. Courtney; Helen E. Edwards; Anthony W. Parker; Kyra Hamilton; Thu Dinh Xuan Pham; Jane O'Brien (BMC, 2018)
Abstract Background Acute hospital services account for the largest proportion of health care system budgets, and older adults are the most frequent users. As a result, older people who have been recently discharged from hospital may be at greater risk of readmission. This study aims to evaluate the comparative effectiveness of transitional care interventions on unplanned hospital readmissions within 28 days, 12 weeks and 24 weeks following hospital discharge. Method The present study was a randomised controlled trial (ACTRN12608000202369). The trial involved 222 participants who were recruited from medical wards in two metropolitan hospitals in Australia. Participants were eligible for inclusion if they were aged 65 years and over, admitted with a medical diagnosis and had at least one risk factor for readmission. Participants were randomised to one of four groups: standard care, exercise program only, Nurse Home visit and Telephone follow-up (N-HaT), or Exercise program and Nurse Home visit and Telephone follow-up (ExN-HaT). Socio-demographics, health and functional ability were assessed at baseline, 28 days, 12 weeks and 24 weeks. The primary outcome measure was unplanned hospital readmission which was defined as any hospital admission for an unforeseen or unplanned cause. Results Participants in the ExN-HaT or the N-HaT groups were 3.6 times and 2.6 times respectively significantly less likely to have an unplanned readmission 28 days following discharge (ExN-HaT group HR 0.28, 95% CI 0.09-0.87, p = 0.029; N-HaT group HR 0.38, 95% CI 0.13-1.07, p = 0.067). Participants in the ExN-HaT or the N-HaT groups were 2.13 and 2.63 times respectively less likely to have an unplanned readmission in the 12 weeks after discharge (ExN-HaT group HR 0.47, 95% CI 0.23-0.97, p = 0.014; N-HaT group HR 0.38, 95% CI 0.18-0.82, p = 0.040). At 24 weeks after discharge, there were no significant differences between groups. Conclusion Multifaceted transitional care interventions across hospital and community settings are beneficial, with lower hospital readmission rates observed in those receiving more transitional intervention components, although only in first 12 weeks. Trial registration Australian and New Zealand Clinical Trial Registry (ACTRN12608000202369).